PD‐1+CD8+ T Cell‐Mediated Hepatocyte Pyroptosis Promotes Progression of Murine Autoimmune Liver Disease - Jie Long; Si‐Yu Yang; Zhen‐Hua Bian; Hao‐Xian Zhu; Min Ma; Xiao‐Qing Wang; Liang Li; Weici Zhang; Ying Han; M. Eric Gershwin; Zhe‐Xiong Lian; Zhi‐Bin Zhao (Advanced Science)
Abstract The specific mechanisms underlying effector pathways in autoimmune liver disease remain enigmatic and therefore constructing appropriate murine models to investigate disease pathogenesis becomes critical. A spontaneous severe murine model of autoimmune liver disease has been previously established in dnTGFβRII Aire−/− mice, exhibiting disease phenotypes that resemble both human primary biliary cholangitis (PBC) and autoimmune hepatitis (AIH). The data suggests that auto‐reactive liver‐specific CD8+ T cells are the primary pathogenic cells in liver injury. In this study, these data are advanced through the use of both single‐cell sequencing and extensive in vitro analysis. The results identify a specific expanded pathogenic subset of PD‐1+CD8+ T cells in the liver, exhibiting strong functional activity and cytotoxicity against target cells. Depletion of PD‐1+CD8+ T cells using CAR‐T cells effectively alleviates the disease. GSDMD‐mediated pyroptosis is found to be aberrantly activated in the livers of model mice, and treatment with a GSDMD‐specific inhibitor significantly inhibits disease progression. In vitro experiments reveal that PD‐1+CD8+ T cells can induce the pyroptosis of hepatocytes through elevated production of granzyme B and perforin‐1. These results provide a novel explanation for the cytotoxic activity of pathogenic liver PD‐1+CD8+ T cells in autoimmune liver diseases and offer potential therapeutic targets.